Identidade e competências profissionais: um estudo com diretores executivos de uma cooperativa de trabalho médico de Minas Gerais - Fatima Ferreira Roquete (2012)
The health system in Brazil is constituted of three interwoven subsystems: the Unified Health system (SUS), public subsystem; the private, direct subsystem payment; and supplementary medical attention or the private health care insurance plans market. In 2012, more than aquarter of the Brazilian population had some kind of supplementary assistance, whereby 36% of these beneficiaries were assisted by 326 Unimed medical work cooperatives, the largest supplementary medical assistance network in Brazil, present in more than 83% of nationalterritory and numbering 112,000 associate doctors. Each Unimed cooperative is independent, being the property of the doctors associated to it and responsible for its management. Factors related to the transformation of the global environment, as well as specific aspects of the national reality, added to cooperative management specificitites, have created a complex working scenario for doctors who become executive directors of a Unimed cooperative. Therefore, the objective of this study was to analyze the configuration of executive director cooperative member identity in a Unimed medical work cooperative, considering theprofessional skills mobilized for the execution of the function. The study scenario was a Unimed cooperative, located in Minas Gerais. 29 profissionals participated, divided into two groups. The primary group was composed of four cooperative-doctors carrying out the function of managers in the cooperative, acting as executive directors. These were the people whose identity and skills we sought to establish and we therefore called them the primary subjects. The second group, called secondary subjects, was composed of 25 professionals whowork alongside the executive director doctors on a daily basis. The study was approved by the UFMG Research Ethics Committee. Data collection was performed in 2011, and an individual interview with semi-structured script was adopted. Before participation, the interviewees signed an Informed Consent Agreement form. In data analysis, the technique of content analysis was used. The author prepared an integrated analysis perspective of identity and professional skills, based on Dubar (1997, 2005) and Cheetham and Chivers (1996, 1998, 2000) adapted by Paiva (2007). In a biographical and relational approach the following wererevealed: the training, previous experience and trajectory of the directors; their current professional work in Unimed, and away from it; the expectations related to the work they perform in their position; and relational identity in their own view and in that of significantothers with whom they share their working day. The results showed that the identity and professional skills of Unimed-Beta executive directors are constructed through everyday work in an interrelated manner, thereby characterizing a dynamic and procedural relation. The professional skills mobilized by the directors in the performance of their function cover asignificant set of skills, inserted in five components from the integrated analysis perspective adopted: cognitive, functional, behavioral, ethical and political. The skills mentioned as belonging to the chief executive officer by the secondary subject doctors and non-doctors were fundamental in comprehending the identity and professional skills mobilized by the directors of a medical work cooperative. The thesis that the identity configuration of Unimed executive director medical cooperative member doctors is related to the mobilization of skillsthat enable challenges to be met in the context of Brazilian health was confirmed.